Pengaruh Kualitas Produk, Perceived Value dan Brand Awareness Terhadap Keputusan Pembelian Konsumen Ventela Footwear di Kota Pasuruan - Muhammad Rizki Ardiansyah; Nuraeni Nuraeni; Khoirul Huda (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This research was conducted with the aim of knowing, explaining and analyzing the influence of product quality, perceived value and brand awareness variables on purchasing decisions either individually or partially or together or simultaneously. The survey was conducted on Ventela footwear consumers in the city of Pasuruan. This research uses multiple linear, whereas based on the method this research is quantitative research. In this study there are three independent variables, namely product quality, perceived value and brand awareness and one related variable, namely purchasing decisions. The population in this study are all consumers who use or are currently purchasing Ventela products. Due to the fact that the population size of this study cannot be known with certainty and there are limited time, effort and costs, an incidental sampling technique of 100 respondents was used. Data analysis was quantitative descriptive using a simple linear regression analysis formula which was processed using the SPSS 25 program. The results of this study indicate that: 1. Product quality variable has a positive and insignificant effect on purchasing decisions, 2. Perceived value variable has a positive and significant effect on Purchasing Decisions 3. Brand awareness variables have a positive and significant effect on Purchase Decisions 4. Product quality, Perceived value and Brand awareness variables have a positive and significant effect on Purchase Decisions.